Ongoing Oscillatory Electrophysiological Alterations in Frail Older Adults: A MEG Study - Suárez-Méndez, Isabel; Walter, Stefan; López-Sanz, David; Pasquín, Natalia; Bernabé, Raquel; Castillo Gallo, Ernesto; Valdés, Myriam; del Pozo, Francisco; Maestú, Fernando; Rodríguez-Mañas, Leocadio (Frontiers in Aging Neuroscience, 2021)
Objective: The role of the Central Nervous System in the pathophysiology of frailty is controversial. We used magnetoencephalography (MEG) to search for abnormalities in the ongoing oscillatory neural activity of frail individuals without global cognitive impairment. Methods: 54 older (≥ 70 years) and cognitively healthy (Mini-Mental State Examination ≥ 24) participants were classified as robust (0 criterion, n = 34) or frail (≥ 3 criteria, n = 20) following Fried’s phenotype. Memory, language, attention, and executive function were assessed through well-validated neuropsychological tests. Every participant underwent a resting-state MEG and a T1-weighted magnetic resonance imaging scan. We performed MEG power spectral analyses to compare the electrophysiological profiles of frail and robust individuals. We used an ensemble learner to investigate the ability of MEG spectral power to discriminate frail from robust participants. Results: We identified increased relative power in the frail group in the mu (p = 0.02) and sensorimotor (p = 0.03) frequencies across right sensorimotor, posterior parietal, and frontal nodes. The ensemble learner discriminated frail from robust participants (area under the curve = 0.73 (95%-CI = 0.49-0.98)). Frail individuals performed significantly worse in the Trail Making Test, Digit Span Test (forward), Rey-Osterrieth Complex Figure, and Semantic Fluency Test. Interpretation: Frail individuals without global cognitive impairment showed ongoing oscillatory alterations within brain regions associated with aspects of motor control, jointly to failures in executive function. Our results suggest that some physical manifestations of frailty might partly arise from failures in central structures relevant to sensorimotor and executive processing.